CAN TAX SANCTIONS AND TAX AMNESTY MITIGATE TAX NON-COMPLIANCE?: EXPERIMENTAL EVIDENCE IN INDONESIA - Kadek Pranetha Prananjaya (Berkala Akuntansi dan Keuangan Indonesia, 2018)
This study examines the tax sanctions policy and the tax amnesty program on the compliance of individual taxpayers who conduct business activities. Based on experimental data with a 2x2 factorial design between subjects, participants who are given high tax sanctions tend to be more obedient than participants who are given low tax sanctions manipulation, as well as with the tax amnesty program, participants tend to be more obedient than if there is no program. tax amnesty. Finally, the interaction results also show significant results but interestingly in a direction that is not in accordance with the hypothesis. It was found that tax compliance can be achieved more effectively when the tax amnesty program is combined with lower tax penalties. This implies that a motivational approach in the form of incentives will be more effective when combined with a motivational approach in the form of low-level threats (low enforcement). This study contributes to the tax compliance literature, especially with the specific topic of tax amnesty.